Energy fluxes, mass balance, and climate sensitivity of the Sutri Dhaka Glacier in the western Himalaya - Oulkar, Sunil N.; Thamban, Meloth; Sharma, Parmanand; Pratap, Bhanu; Singh, Ajit T.; Patel, Lavkush Kumar; Pramanik, Ankit; Ravichandran, M. (Frontiers in Earth Science, 2022)
Various regional climatic factors influence glacier mass balance and thus, control the water budget of the Himalayan rivers. However, the scarcity of observational data hinders a detailed understanding of the processes governing glacier mass balances in the Himalaya. Here we analyze the mass balance of Sutri Dhaka Glacier, a debris-free glacier in the Chandra basin (western Himalaya) combining field observations and a physically-based model to understand the drivers of mass balance variability. The modeled energy flux showed that net shortwave radiation contributed 56% to the total surface energy fluxes, followed by net longwave radiation (27%), sensible heat (8%), latent heat (5%), and ground heat flux (4%). However, over the ablation zone, inward fluxes account for most of the total heat flux, resulting in strong summertime melting. The model estimated glacier mass balance was -1.09 ± 0.31 and -0.62 ± 0.19 m w.e. during 2015/16 and 2016/17 that matches well with the in-situ glaciological mass balance of -1.16 ± 0.33 and -0.67 ± 0.33 m w.e., respectively. A sensitivity analysis demonstrates that the mass balance of the glacier is affected by both air temperature (-0.21 m w.e. a-1 °C-1) and precipitation (0.19 m w.e. a-1 (10%)-1) changes. Our study suggests that, the mass balance of Sutri Dhaka Glacier is less sensitive to changes in the partitioning of precipitation into snow and rain because the majority of precipitation falls as snow during the winter when the temperature is well below 0°C.